The influence of stabilizing agents on physicochemical properties of selenium nanoparticles obtained by chemical reduction - Filipović Nenad R.; Stojanović Zoran S.; Stevanović Magdalena M. (Tehnika, 2021)
Selenium nanoparticles (SeNPs) are specific form of this element that has recently become the subject of numerous research, especially in the field of biomedicine. Several synthesis procedures for obtaining SeNPs have been developed so far, among those including reduction of selenium salts are the most frequently used. In this work, it is examined the effect of two stabilizing agents on morphology, size, and crystallinity of obtained SeNPs. For this purpose, bovine serum albumin (BSA) and polyglutamic acid (PGA) were used as stabilizing agents while reduction of sodium selenite with ascorbic acid was elected as a synthesis procedure. Based on the results obtained from scanning electron microscopy (FESEM), transmission electron microscopy (TEM), energy-dispersive X-ray spectroscopy (EDS), selected area electron diffraction (SAED), and measurements of zeta potential, it was determined that the mechanism of stabilization i.e. choice of stabilizing agent can promote different crystalline arrangement within SeNPs. The BSA proved as a more effective stabilizing agent for SeNPs, as it provides obtaining the smaller, more uniform, and amorphous nanoparticles.